Neurocognitive Functioning in Pediatric Craniopharyngioma: Performance before Treatment with Proton Therapy - Fournier-Goodnight, Ashley S. (J Neurooncol, 2017)
The goal of this study was to investigate the impact of patient-, disease-, and treatment-related variables upon neurocognitive outcomes in pediatric patients with craniopharyngioma prior to treatment with proton therapy or observation after radical resection. For all participants (N=104), relevant clinical and demographic variables were attained and neurocognitive evaluations completed prior to irradiation or planned observation. One-sample t-tests were conducted to compare performance to published normative data. Linear models were used to investigate predictors of performance on measures where performance was below normative expectations. Participants showed poorer performance in comparison to the normative group across neurocognitive domains including executive functions (e.g., working memory; Wechsler Digit Span Backward p=0.03), learning and memory (e.g., California Verbal Learning Test [CVLT] Total T p=0.00), and fine-motor coordination (e.g., Grooved Pegboard Dominant Hand p=0.00). Poor performance across areas was predicted by presurgical hypothalamic involvement (e.g., Behavior Rating Inventory of Executive Function Working Memory Index Grade 2 β=−7.68, p=0.03; CVLT Total T Grade 2 β=7.94, p=0.04; Grade 3 β=−9.80, p=0.00), extent of surgery (e.g., CVLT Total T Resection β=−7.77, p=0.04; Grooved Pegboard Dominant Hand β=−1.58, p=0.04), and vision status (e.g., CVLT Total T Reduced vision without impairment β=−10.01, p=0.02; Grooved Pegboard Dominant Hand Bilateral field defect β=−1.45, p=0.01; Reduced vision without impairment β=−2.30, p=0.00). This study demonstrated that patients with craniopharyngioma show weaker neurocognitive performance in comparison to the normative population resulting from tumor, events leading to diagnosis, and early surgical intervention. Systematic investigation of neurocognitive performance before treatment with radiation therapy is essential to evaluating the potential risks and benefits of newer methods of radiation therapy including proton therapy.